An Analysis of English for Maritime Teaching-Learning Process in Politeknik Maritim Negeri Indonesia - Herdiansyah, Ganda; Herdawan, Deri (PPPM Polimarin, 2024)
English is still used as a foreign language in Indonesia. Withstanding its status as a foreign language, it describes the situation where students are learning English in order to communicate with other English speakers in the world when the students may be tourists or business people. Due this consideration, the English language has not been used on a daily basis in the contrary, but only at a particular place and occasion like at an English class at school or on business meeting at an international company. This research sets to examine and describe the method and activity used by the lecturer in the teaching-learning process. The research conducted in Teknika class at the third semester of Politeknik Maritim Negeri Indonesia (Polimarin) Semarang. In this research, the researcher used qualitative research. In collecting the data, the researcher used observation, specifically as a nonparticipant observer. After conducting the research and analyzing the data collected through observation, the researcher knew the teaching method used by the lecturer was CBI while the learning activities were IBLL and role play. It can be seen that the lecturer focused on the speaking skill in the teaching-learning process